The Role of Universities in Promoting Intellectual Security: A Field Study on a Sample of Students at the University of Sharjah - Alkarbi, Noura; Kaouache, Raouf; Al-Ali, Ahmed (Al-Adab Journal, 2026)
Universities play a crucial role in fostering individual and societal well-being while contributing to citizenship and intellectual security. This study investigates the role of the University of Sharjah in promoting intellectual security from the perspective of its students. Specifically, it examines the contributions of faculty members, student activities, and academic curricula in reinforcing intellectual security. Employing a descriptive survey methodology, the study utilized a structured questionnaire to collect data from a purposive random sample of 80 male and female students at the University of Sharjah. The findings indicate that faculty members play a pivotal role in promoting moderate Islamic values and guiding students toward credible sources of information, thereby mitigating the spread of misinformation. This highlights the university’s commitment to fostering an educational environment that encourages critical thinking and intercultural respect within the United Arab Emirates. Additionally, student activities were found to enhance values of tolerance and national identity, providing students with opportunities to develop social and personal skills through dialogue and idea exchange. Furthermore, the curricula incorporate scientific content that strengthens students’ ability to navigate contemporary intellectual challenges, fostering dialogue and critical thinking skills essential for an informed and resilient generation. The results also revealed no statistically significant differences between male and female students’ perceptions of the university’s role in promoting intellectual security. However, students’ cumulative GPA was found to influence their assessment of the university’s efforts in this regard. Based on these findings, the study recommends establishing platforms for open dialogue within the university to facilitate discussions on intellectual security, conducting periodic evaluations of academic activities and programs, and regularly reviewing opinion polls to refine institutional strategies.